Prototipe Sistem Penyiraman Dan Pengaturan Volume Air Otomatis Berbasis Internet Of Things Pada Landscape Building Management Bina Nusantara - Agung Saputra; Sejati Waluyo; Wahyu Pramusinto (CV. Multi Kreasi Media, 2025)
Landscape is a plant maintenance, care and renovation service. In the process of plant care, diligence and consistency are needed in keeping plants alive properly. Problems that are often encountered in this plant care service are less than optimal care including uneven watering of chili plants, this is caused by the watering process which is still done manually without paying attention to soil moisture conditions and temperature at the time of watering. Manual watering can be forgotten or not done by the chili plant nurse and watering is uneven without paying attention to the amount of water needed. Therefore, an automatic plant watering system is needed on a scheduled basis and the volume of watering water is regulated according to soil moisture and air temperature. The research method uses the waterfall method to produce a system that suits user needs. The results of testing the watering system and setting the volume of watering water based on the IoT watering system can work based on input from the humidity sensor and watering schedule obtained from the database with a delay of 1 to 3 seconds and an accuracy level of 90% watering water volume with 10 trials.